Viability-Based Computations of Solutions to the Hamilton-Jacobi-Bellman Equation - Bayen, Alexandre M.; Claudel, Christian; Saint-Pierre, Patrick (Hybrid Systems, 2007)
This article proposes a new capture basin algorithm for computing the numerical solution of a class of Hamilton-Jacobi-Bellman (HJB) partial differential equations (PDEs) [3], based on a Lax-Hopf formula [2]. The capture basin algorithm is derived and implemented to perform numerical computations. Its performance is measured with highway data obtained for interstate I80 in California.